Knowledge, Attitude and Practice Regarding Dengue Fever among the Healthy Population of Highland and Lowland Communities in Central Nepal - Dhimal, Meghnath (Public Library of Science, 2014)
BACKGROUND: Dengue fever (DF) is the most rapidly spreading mosquito-borne viral disease in the world. In this decade it has expanded to new countries and from urban to rural areas. Nepal was regarded DF free until 2004. Since then dengue virus (DENV) has rapidly expanded its range even in mountain regions of Nepal, and major outbreaks occurred in 2006 and 2010. However, no data on the local knowledge, attitude and practice (KAP) of DF in Nepal exist although such information is required for prevention and control measures. METHODS: We conducted a community based cross-sectional survey in five districts of central Nepal between September 2011 and February 2012. We collected information on the socio-demographic characteristics of the participants and their knowledge, attitude and practice regarding DF using a structured questionnaire. We then statistically compared highland and lowland communities to identify possible causes of observed differences. PRINCIPAL FINDINGS: Out of 589 individuals interviewed, 77% had heard of DF. Only 12% of the sample had good knowledge of DF. Those living in the lowlands were five times more likely to possess good knowledge than highlanders (P<0.001). Despite low knowledge levels, 83% of the people had good attitude and 37% reported good practice. We found a significantly positive correlation among knowledge, attitude and practice (P<0.001). Among the socio-demographic variables, the education level of the participants was an independent predictor of practice level (P<0.05), and education level and interaction between the sex and age group of the participants were independent predictors of attitude level (P<0.05). CONCLUSION: Despite the rapid expansion of DENV in Nepal, the knowledge of people about DF was very low. Therefore, massive awareness programmes are urgently required to protect the health of people from DF and to limit its further spread in this country.